1998
DOI: 10.1080/135457098338572
|View full text |Cite
|
Sign up to set email alerts
|

National Working-Time Regimes and Equal Opportunities

Abstract: Progress towards equal opportunities is critically dependent upon the development of a more equal and more balanced allocation of time in both paid and unpaid work. Gender divisions relating to working time arise primarily from differences in gender divisions within the household but the extent and form that these gender divisions take in the labor market are moderated or mediated by national working-time regimes. These regimes are found to be extremely diverse across Europe with very different implications fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 3 publications
4
84
1
1
Order By: Relevance
“…Across the EU 15, 71 per cent of working age men are in employment compared with 51 per cent of women. That 33 per cent of women in employment are working part-time compared with 6 per cent of men suggests that women still accommodate unpaid family work (Eurostat, 2000: 34;Bettio et al, 2000;Fagan et al, 2001;Hakim, 2000;Rubery et al, 1998aRubery et al, , 1998bRubery et al, , 1999). Men's lifetime earnings are higher than their partners': in the UK among couples with children -on average -women's earnings are half men's (Rake, 2000).…”
Section: Paid Workmentioning
confidence: 99%
“…Across the EU 15, 71 per cent of working age men are in employment compared with 51 per cent of women. That 33 per cent of women in employment are working part-time compared with 6 per cent of men suggests that women still accommodate unpaid family work (Eurostat, 2000: 34;Bettio et al, 2000;Fagan et al, 2001;Hakim, 2000;Rubery et al, 1998aRubery et al, , 1998bRubery et al, , 1999). Men's lifetime earnings are higher than their partners': in the UK among couples with children -on average -women's earnings are half men's (Rake, 2000).…”
Section: Paid Workmentioning
confidence: 99%
“…Lallement noted in this journal in 2011 that levels of unemployment, and societal labour market adjustments to job loss, varied substantially across nations, but he suggested that part of what marked the UK out was its postrecessionary growth in 'work-time underemployment'. An increase in the number of workers with 'too few' hours raises questions about recessionary ramifications for the UK work-time regime (Rubery et al, 1998). These are also class concerns: work-time and work-time preferences are classed in Britain.…”
Section: Introductionmentioning
confidence: 99%
“…Lewis 1992, Sainsbury 1994, Drew et al 1998; as well as more specific studies of working-time regimes and work-family reconciliation measures (e.g. Anxo and O'Reilly 2002, O'Reilly and Fagan 1998, Rubery et al, 1998, den Dulk et al 2001. However, in this analysis we advance the debate in two ways.…”
Section: Introductionmentioning
confidence: 99%